Anti-Breast Cancer Activity of Bergenin and Naringenin on Michigan Cancer Foundation-7 Cells: An In-Vitro Study - Urvashi Sharma, (Asian Journal of Pharmaceutics (AJP), 2025)
Breast cancer is among the biggest causes of mortality for women around the globe. The treatment of breast cancer usually involves surgical procedure or chemotherapy but nature offers potentially safer and more effective treatment options. Using the MTT assay, this study evaluates the cytotoxic effects of Bergenin (Berg) and Naringenin (NG) on Michigan cancer foundation-7 (MCF-7), a human breast cancer cell line. Materials and Methods: Breast cancer cells, MCF-7 cells were treated with several concentrations of Berg and NG and the MTT assay was used to measure cell viability, from which half-maximal inhibitory concentration (IC50) values were calculated to measure cytotoxicity. Findings: The cytotoxic effect of both drugs was dose dependent. IC50 value was of Berg was 135.06 μg/mL, but NG’s was 114.59 μg/mL, indicating a higher cytotoxic effect. Potential mechanisms for the observed effects include reactive oxygen species production, cell cycle arrest, apoptosis activation, and modification of the estrogen receptor and survival signaling pathways. Conclusion: When it comes to MCF-7 breast cancer cells, Berg and NG exhibit moderate but noteworthy anti-proliferative action. Their promise as lead compounds for additional research in breast cancer therapy is highlighted by their natural origin and multi-targeted modes of action. To confirm their therapeutic value, more mechanistic and in-vivo research is advised.